Rätten till Norrland - Oskarsson, Johan; Busk, Martin (2007)
An introduction to the complexity which surrounds the matters of land in the northern parts of Sweden was the purpose of this thesis. The agriculture colonization, the delimitation and the development of forestry and mining business were big events which are shown from the view of property rights. The situation of the Lappish people and how their situation has changed through the history was the main theme of the thesis. Hopefully this thesis will also serve as a support while reading for example investigations published by the government and judgments by courts. Supply to the resources of nature has always been decisive for the survival of humans. Already during the time when the first people immigrated to Scandinavia these people's migrating were ruled by the supply of wild animals. The structures that laid the foundations of our regulated society were formed during the time while the human population gradually grew. When more and more people were dependant of the same resources it lead to more conflicts and with that the need of a regulated society. Family groups, clans, people land, provinces and countries were established as people formed collectives. During the 14th century a legible central power arose in the shape of a royal family which by the use of different tools of power controlled a large part of the population. The foundation of the society was a more developed agriculture. The Lappish people had developed a different organisation in the interior parts of northern Sweden which was adapted to their own life conditions. Several family groups formed collectives with the aim of making hunting more effective to secure their survival. This new system was called the sijdda society. The first documented contacts between these two different forms of societies were performed through the so called birkarla men who were trading with the Lappish people. During the 14th century it was a common opinion that the King had the legality to impose taxes upon the birkarla men. During the 16th century these two forms of societies more frequently began to run into each other. The state of Sweden perceived the development in the northern parts principally from an economic point of view and was alternately supporting the interest group that generated most incomes by taxes. In the southern parts of Sweden the growth of the population had led to a lack of land and the cultivation spread towards the north. This process then followed the river valleys westwards from the already cultivated coastlands. The more powerful central power stimulated the colonization because of its effect in generating bigger incomes by taxes. The society kept on developing by for example establishing of authorities, establishment of different tax systems, and by carrying out national registrations. The Lappish society was forced to adapt to the Swedish society orders. The Swedish society's presence and interest in the northern parts increased with occurrence of mining and forests. The agriculture colonization gradually increased to its extent. Land use performed by the Lappish by reindeer breeding, hunting and fishing was during the 17th century until the middle of the 18th century considered to maximizing the benefit of society. Tax systems and other regulations which were performed by the Swedish state all influenced the Lappish, likewise were changes in reindeer herding methods affected by different tax systems. From the mid 18th century the position of the Lappish people deteriorated in favour of agriculture. They were more marginalized and rights, which earlier had been respected by the society, now were decreased. During the 18th and 19th centuries the delimitation was performed which was a far-reaching reform with focus on property rights with the main purpose to separate private land from public land. An expanding mining and timber industry had preference in the delimitation process above both farmers and Lappish. Public interests were represented by the Swedish state and were in many cases prioritized and thus private interests were in many cases reduced. The delimitation-functions rendered possibilities for increased cultivation and with that possibility for more people to earn one's living. Privileges which were given industries made their expansion possible. The consequences of delimitation for the Lappish were obviously negatively while their property rights were considered as non-existent during this process. In the concluding part of the reform some considerations were taken to the Lappish. But their possibilities to perform their traditional work had deteriorated dramatically. The Lappish culture in general and especially reindeer herding were, from a public point of view, close to extinction. During the time while reindeer herding still existed it was considered as necessary to regulate the relation between the Lappish lifestyle and the farming population. The first reindeer-pasturage-law was founded in 1886 and together with its three following Lappish individual rights to land and water was definitively rubbed out and was replaced with "Lappish-privileges" which were common for a larger Lappish group. Reindeer herding was considered as the biggest reason for conflicts with farmers. Reindeer herders and herding got a very advanced position compared with other Lappish groups during the political process which surrounded the legislation. The whole legislation was built on patriarchal ideas about Lappish and the legislators where periodically influenced both by racist ideas and hierarchic ideas of civilization. This law has strongly formed the Lappish branch of business during the 20th century and was founded with the settled farmer as a point of departure. The reindeer-herding-law has always been affected by international circumstances and a clear example is the movements through compulsion of Lappish and reindeers from the Karesuando area during 1920 – 1930. The reason was changes in possibilities to reindeer-pasturage in Norway. The immigrated Lappish introduced the extensive form of reindeer herding which pushed the intensive herding aside. The present law from 1971 is a developed version of the old laws and can with reason be considered to rest on an antiquated valuation. The law has caused a cleavage within the Lappish group because of its one-sided focus on the reindeer-herding Lappish. Recent law is keeping this focus referring to reindeer-herding as a front preserver of Lappish culture. Lappish who are standing outside off reindeer-herding have small possibilities to enter the industry and with that take part of the benefits that follows reindeer-herding, because of the systems strong limitation. The Lapps are today acknowledged as an ethnic minority, an original population, and reindeer-herding is classified as a national interest. The law which once was formed to regulate the relations between reindeer-herding and the world around today has the purpose to preserve the Lappish culture, a culture that the law in many cases has formed.